Deviant behavior - Humphrey, John A.; Schmalleger, Frank (Los Angeles : SAGE, 2021)
"What makes behavior deviant and who gets to decide what deviance is? Deviant Behavior seeks to answer these questions and more. This compelling text is for undergraduate students who are curious about the social forces that shape deviance, the motivations and consequences of deviant behaviors, and how our definition of deviance changes over time. Authors Jack Humphrey and Frank Schmalleger discuss a wide range of deviant behaviors - from criminal acts to extreme forms of typical behavior - and provide the necessary foundation to understand the impact of globalization on traditional and emerging forms of deviance. Students will explore deviance in our modern world using a systematic application of social and criminological theories to a range of deviant behaviors, including cyberdeviance and positive deviance, to help them better understand themselves, others, and their society"--
Includes bibliographical references (pages 297-310) and index.
Keywords: Deviant behavior